APPLYING Z-SCORE MODEL TO PREDICT DELISTING IN INDONESIAN COMPANIES - Febrina Suryadi, Vany
Business activities have been important pillars in every country. With the growing amount of big corporations in Indonesia, it is fundamental to develop a delisting predictor as a tool of warning for both managers and investors. Hence, this study is aimed to develop a model in which it can predict the probability of delisting in a company through a series of financial ratios. Delisting itself can occur voluntarily or involuntarily and happen when a company declares bankruptcy, terminate their operation, wish to go private or simply not meet the requirement to be listed anymore. Using a total sample of 256 firms in Indonesia between 1990 and 2017 taken from the Bloomberg terminal a model was developed through multivariate discriminant analysis. The resulting model was tested to out of sample data and yield an adequate result. Further research is needed to develop an even more accurate delisting model through newer analysis method